Low-Temperature Deformation and Fracture of Cr-Mn-N Stainless Steel: Tensile and Impact Bending Tests; Metals; Vol. 13, iss. 1 - Narkevich N. A. Nataljya Arkadjevna; Vlasov I. V. Iljya Viktorovich; Volochaev M. N. Mikhail Nikolaevich; Gomorova Yu. F. Yuliya Fedorovna; Mironov Yu. P. Yury Petrovich; Panin A. V. Alexey Viktorovich; Berto F. Filippo; Maksimov P. V. Pavel Vasiljevich; Deryugin E. E. Evgeny Evgenjevich (2023, 2023)
Title screen